Measuring market liquidity risk - which model works best? - Cornelia Ernst; Sebastian Stange; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
Market liquidity risk, the difficulty or cost of trading assets in crises, has been recognized as an important factor in risk management. Literature has already proposed several models to include liquidity risk in the standard Value-at-Risk framework. While theoretical comparisons between those models have been conducted, their empirical performance has never been benchmarked. This paper performs comparative back-tests of daily risk forecasts for a large selection of traceable liquidity risk models. In a 5.5 year stock sample we show which model provides most accurate results and provide detailed recommendations which model is most suitable in a specific situation.
Keywords: G11; G12; G18; G32; 330; asset liquidity; liquidity cost; price impact; Xetra liquidity measure (XLM); risk measurement; Value-at-Risk; market liquidity risk